GAGASAN ARTIFICIAL INTELLIGENCE DALAM PENERAPAN HUKUM DI ERA 4.0 PERSPEKTIF PENYELESAIAN PERKARA MODEL RESTORASI JUSTICE DAN HUKUM PROGRESIF - anshori, anshori (Legal Studies Journal, 2022)
This article tries to analyze the idea of artificial intelligence (AL) as a form of internet-based technology development, in the perspective of justice restoration theory and progressive law. The method used in this research is normative juridical with a theoretical approach and legal concept. The principles contained in the concept of restoration of justice and progressive law as an approach in resolving legal cases that occur, function as an analytical tool for artificial intelligence operations in resolving a legal case that occurs. Al's operations in solving cases were not parallel or in the same breath with the principles of restoration of justice and progressive law.Keyword: Artificial intelligence, Restoration of Justice, Progressive Law